Número racional não negativo na forma fracionária : sentido atribuído por alunos do 6º ano do ensino fundamental - Gaviraghi, Analucia (2013)
The main objective of this work is to investigate how students in the 6th grade of Elementary School deal with problem situations involving non-negative rational numbers in its fractional form, in their different meanings. The data were generated from the collection and description of the plans and the proposed teaching of non-negative rational number in its fractional representation in the 5th and 6th years of Elementary School, and also a research instrument with nine questions covering five concepts: part-whole, quotient, number, extent and multiplicative operator. The study subjects were 11 students in the 6th grade of Elementary School at a state school in the city of Coronel Bicaco/RS. The analyzes were performed based on established dialogues with theoretical frameworks located in Caraça (1986), Nunes et al. (2003) and Duval (2003). The collected data reveal that students demonstrate that they have assigned signification to some meanings, such as extent and multiplicative operator rational number in its fractional representation, while in others have difficulty in identifying and representing the mathematical object